2022
DOI: 10.1097/md.0000000000031071
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of the clinical significance of HLA class II in breast cancer

Abstract: Human leukocyte antigen (HLA) class II plays critical roles in antigen presentation and the initiation of immune responses. However, the correlation between the HLA class II gene expression level and the survival of patients with breast cancer is still under investigation. We analyzed microarray and RNA-Seq data of breast cancer from the cancer genome atlas (TCGA), genotype-tissue expression (GTEx) and Oncomine databases by using bioinformatics tools. The expression of the HLA-DQA1, HLA-DQA2, and HLA-DQB2 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Taking the survival analysis of CD48 in the TCGA-BRCA dataset in the TCGA database and the GSE26304 breast cancer dataset in the GEO database as examples, the user obtains the results shown in Figures 3A and B. The CD48 high expression group in both datasets had a longer overall survival (OS), which validated the previous findings[28].…”
Section: Resultssupporting
confidence: 77%
“…Taking the survival analysis of CD48 in the TCGA-BRCA dataset in the TCGA database and the GSE26304 breast cancer dataset in the GEO database as examples, the user obtains the results shown in Figures 3A and B. The CD48 high expression group in both datasets had a longer overall survival (OS), which validated the previous findings[28].…”
Section: Resultssupporting
confidence: 77%
“…Additionally, GDI2 is a target of paclitaxel through the p75NTR signaling pathway in prostate cancer tumorigenesis [ 23 ]. HLA-DQB2 has been shown to be highly expressed in breast cancer and predicts better overall survival [ 24 ]. Plasma HSP90AA1 has been found to predict the risk of breast cancer incidence and distant metastasis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we found a statistically significant association between rare binned HLA-DPB1 alleles (HLA-DPB1*09:01, HLA-DPB1*10:01, HLA-DPB1*106:01, HLA-DPB1*18:01, HLA-DPB1*20:01, HLA-DPB1*26:01, HLA-DPB1*28:01, HLA-DPB1*296:01, and HLA-DPB1*55:01) and young age at cancer diagnosis, additional investigation for these HLA alleles in a large cohort of LSVH is required to further complement and validate our findings. While HLA class II is traditionally associated with presenting antigens from extracellular pathogens, it also plays a role in presenting tumor antigens [ 56 , 57 ]. It has been reported that HLA class II antigen expression by tumor cells can influence the tumor antigen (TA)-specific immune responses [ 56 ].…”
Section: Discussionmentioning
confidence: 99%